Responding to the Humanitarian Crisis in Gaza: Damned if You do... Damned if You don't! - Theresa Farhat; Sarah Ibrahim; Zahi Abdul-Sater; Ghassan Abu-Sittah (Ubiquity Press, 2023)
Palestine, since 1948, has endured frequent military occupations and uprisings, intifadas, in a limited geographic area that has resulted in one of the worst humanitarian crises. The prolonged nature of this military occupation has created a biosphere of war that is uninhabitable, whereby Palestinians suffer from physical, psychological, and social wounds. Israel also imposed restrictive measures in Gaza, making it difficult for Palestinians to obtain permits to work and travel throughout Palestine. Israel continued to intensify the restrictions on Gaza, reaching a blockade on the Gaza Strip, which cut off Palestinians from Jerusalem, where hospitals, banks, and vital services are found. This form of permanent siege resulted in a surge in the unemployment rate, poverty, and poor nutritional and wellbeing status. The siege also resulted in the largest open-air prison, as people became stuck between an incomplete life and the absence of total death. The major challenge is that humanitarian interventions, in the case of Gaza, are ineffective, as they are part of the siege framework. This is because any humanitarian aid meant for Gaza needs to be approved by Israel. Thus, when the emergency becomes chronic and humanitarian interventions become part of the siege framework, how can Gaza rebuild its health capacity in a permanent emergency, and to what extent can the humanitarian sector make a change?